Investigating the Role of Interpretation Bias in Mindfulness-Based Treatment of Adults With Generalized Anxiety Disorder - Hoge, Elizabeth A.; Reese, Hannah E.; Oliva, Isabelle A.; Gabriel, Caroline D.; Guidos, Brittany M.; Bui, Eric; Simon, Naomi M.; Dutton, Mary Ann (Frontiers in Psychology, 2020)
Although mindfulness-based interventions (MBIs) have garnered empirical support for a wide range of psychological conditions, the psychological processes that mediate the relationship between MBIs and subsequent symptomatic improvement are less well-understood. In the present study we sought to examine, for the first time, the relationship between mindfulness, negative interpretation bias as measured by the homophone task, and anxiety among adults with Generalized Anxiety Disorder (GAD). Forty-two individuals with GAD completed measures of mindfulness, interpretation bias, and anxiety before and after treatment with Mindfulness-based Stress Reduction (MBSR). Contrary to prior research, we did not find evidence of an indirect relationship between baseline levels of mindfulness and anxiety via negative interpretation bias. MBSR did result in significant reductions in negative interpretation bias from baseline to post-treatment; however, we did not find evidence of an indirect relationship between changes in mindfulness and changes in anxiety via changes in interpretation bias. Taken together, these results provide minimal support for the hypothesized relationship between mindfulness, negative interpretation bias, and anxiety among adults with GAD. Limitations and specific suggestions for further inquiry are discussed.